Genetic diversity of Gymnocypris firmispinatus: Insights from microsatellites and mitochondrial DNA among wild, broodstock source, and broodstock populations - Huke He; Haifeng Tian; Xiaodong Wang; Liang Peng; Liqiao Zhong; Pengzhi Qi; Baoshan Ma (Aquaculture Reports)
This study provides an analysis of the genetic diversity and population structure of Gymnocypris firmispinatus, a fish species endemic to the upper Yangtze River. Genetic evaluations were conducted using both microsatellite and mitochondrial DNA (mtDNA) markers across three distinct populations: wild, broodstock source, and broodstock. The results show that genetic diversity is relatively uniform across these groups, with no significant differences observed in diversity levels. The wild population had an average of 15.889 alleles per locus, the broodstock source population had an average of 16.444 alleles per locus, and the broodstock population had an average of 13.778 alleles per locus, with an average polymorphic information content (PIC) of 0.883. The observed heterozygosity (Ho) and expected heterozygosity (He) averaged 0.729 and 0.894, respectively. mtDNA (5’-Cyt b + D-loop-3’) analysis revealed 36 haplotypes with an overall haplotype diversity (h) of 0.901 and an overall nucleotide diversity (π) of 0.00476. Genetic differentiation was significant, particularly between the wild and broodstock populations, as indicated by high Fst values for both microsatellite and mtDNA markers. The broodstock population presented a high level of diversity with microsatellite markers (Ho = 0.737, He = 0.798, PIC = 0.769), whereas mtDNA markers presented comparatively lower diversity (h = 0.563, π = 0.00079). This contrast highlights the importance of using both marker types to gain a complete understanding of the genetic structure of populations. The reduced mtDNA diversity is likely due to its smaller effective population size and greater susceptibility to genetic drift, given its maternal inheritance. These findings suggest that stock enhancement release activities can help preserve the genetic diversity of the G. firmispinatus population.